1997
DOI: 10.3310/hta1110
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for inborn errors of metabolism: a systematic review.

Abstract: Newborn screening for inborn errors of metabolism: a systematic review. Health Technol Assessment 1997; 1(11). NHS R&D HTA Programme T he overall aim of the NHS R&D Health Technology Assessment (HTA) programme is to ensure that high-quality research information on the costs, effectiveness and broader impact of health technologies is produced in the most efficient way for those who use, manage and work in the NHS. Research is undertaken in those areas where the evidence will lead to the greatest benefits to pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 114 publications
(187 reference statements)
0
127
0
2
Order By: Relevance
“…One of the reviews ÔNewborn screening for inborn errors of metabolism: a systematic reviewÕ applied the Wilson and Junger criteria to a number of inborn errors which included PKU, maple syrup urine disease, homocystinuria, tyrosinaemia type 1, galactosaemia, methylmalonic acidaemia, propionic acidaemia, isovaleric acidaemia, glutaric aciduria type 1, hydroxymethylglutaric aciduria, mitochondrial respiratory chain disorders, medium-chain acyl-CoA dehydrogenase (MCAD) deficiency, long-chain fatty acid oxidation disorders, multiple acyl-CoA dehydrogenase deficiency, congenital adrenal hyperplasia, familial hypercholesterolaemia, peroxisomal disorders, urea cycle disorders, biotinidase deficiency, Wilson disease, molybdenum co-factor deficiency, disorders of purine and pyrimidine metabolism and lysosomal storage disorders [7]. On the basis of this assessment, the review concluded that universal neonatal screening for PKU is worthwhile and should be continued, that national programmes for profound biotinidase deficiency and congenital adrenal hyperplasia are justified, and that screening should be seriously considered for MCAD and glutaric aciduria type 1.…”
Section: Uk Health Technology Assessmentsmentioning
confidence: 99%
“…One of the reviews ÔNewborn screening for inborn errors of metabolism: a systematic reviewÕ applied the Wilson and Junger criteria to a number of inborn errors which included PKU, maple syrup urine disease, homocystinuria, tyrosinaemia type 1, galactosaemia, methylmalonic acidaemia, propionic acidaemia, isovaleric acidaemia, glutaric aciduria type 1, hydroxymethylglutaric aciduria, mitochondrial respiratory chain disorders, medium-chain acyl-CoA dehydrogenase (MCAD) deficiency, long-chain fatty acid oxidation disorders, multiple acyl-CoA dehydrogenase deficiency, congenital adrenal hyperplasia, familial hypercholesterolaemia, peroxisomal disorders, urea cycle disorders, biotinidase deficiency, Wilson disease, molybdenum co-factor deficiency, disorders of purine and pyrimidine metabolism and lysosomal storage disorders [7]. On the basis of this assessment, the review concluded that universal neonatal screening for PKU is worthwhile and should be continued, that national programmes for profound biotinidase deficiency and congenital adrenal hyperplasia are justified, and that screening should be seriously considered for MCAD and glutaric aciduria type 1.…”
Section: Uk Health Technology Assessmentsmentioning
confidence: 99%
“…An undiagnosed or delayed diagnosed hearing impairment may have serious effects on a child's language, social, emotional, cognitive, academic, and vocational development, significantly affecting the child's quality of life [1][2][3][4][5]. This fact becomes more important in health systems when we take into account the high incidence of hearing impairment among newborns: current Universal Newborn Hearing Screening (UNHS) statistics indicate an overall hearing loss rate of 1-3/1,000 live births and 2-4/100 in neonatal intensive care units [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…strategies to detect a maximal number of treatable metabolic disorders is a major challenge for preventive medicine [3,10]. Among other factors, early diagnosis and treatment are crucial determinants for outcome in many genetic metabolic diseases [2,12].…”
mentioning
confidence: 99%